Synthesis and Structure Elucidation of Novel Spirooxindole Linked to Ferrocene and Triazole Systems via [3 + 2] Cycloaddition Reaction - Mezna Saleh Altowyan; Saied M. Soliman; Matti Haukka; Nora Hamad Al-Shaalan; Aminah A. Alkharboush; Assem Barakat (Molecules, 2022)
In the present work, a novel heterocyclic hybrid of a spirooxindole system was synthesized via the attachment of ferrocene and triazole motifs into an azomethine ylide by [3 + 2] cycloaddition reaction protocol. The X-ray structure of the heterocyclic hybrid (1″R,2″S,3R)-2″-(1-(3-chloro-4-fluorophenyl)-5-methyl-1H-1,2,3-triazole-4-carbonyl)-5-methyl-1″-(ferrocin-2-yl)-1″,2″,5″,6″,7″,7a″-hexahydrospiro[indoline-3,3″-pyrrolizin]-2-one revealed very well the expected structure, by using different analytical tools (FTIR and NMR spectroscopy). It crystallized in the triclinic-crystal system and the P-1-space group. The unit cell parameters are a = 9.1442(2) Å, b = 12.0872(3) Å, c = 14.1223(4) Å, α = 102.1700(10)°, β = 97.4190(10)°, γ = 99.1600(10)°, and V = 1484.81(7) Å3. There are two molecules per unit cell and one formula unit per asymmetric unit. Hirshfeld analysis was used to study the molecular packing of the heterocyclic hybrid. H···H (50.8%), H···C (14.2%), Cl···H (8.9%), O···H (7.3%), and N···H (5.1%) are the most dominant intermolecular contacts in the crystal structure. O···H, N···H, H···C, F···H, F···C, and O···O are the only contacts that have the characteristic features of short and significant interactions. AIM study indicated predominant covalent characters for the Fe–C interactions. Also, the electron density (ρ(r)) at the bond critical point correlated inversely with the Fe–C distances.